2021
DOI: 10.1016/j.marenvres.2020.105231
|View full text |Cite
|
Sign up to set email alerts
|

Rapid recovery of native habitat-builders following physical disturbance on pier pilings offsets colonization of cryptogenic and non-indigenous species in a Chilean port

Abstract: Rapid recovery of native habitat-builders following physical disturbance on pier pilings offsets colonization of cryptogenic and non-indigenous species in a Chilean port.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 94 publications
1
4
0
Order By: Relevance
“…These biases are generally attributed to the legacy of species association with human‐made and disturbed habitats embedded in dispersal networks (Pearson, Ortega, Eren, & Hierro, 2018; Pyšek et al, 2015). As such, and although this may be counter‐intuitive on a first sight (Price & Pärtel, 2013), our findings are not in contradiction with the limiting similarity concept (MacArthur & Levins, 1967): the mechanisms of biotic resistance involving functional similarity (notably through competition) are indeed undermined by disturbance (Elton, 1958) as demonstrated with our model community (Leclerc et al, 2021). Importantly, our model community is also composed of multiple foundation species and prone to complex epibioses involving neutral to positive interactions, which also affect its invasibility (Bulleri et al, 2008; Leclerc & Viard, 2018).…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…These biases are generally attributed to the legacy of species association with human‐made and disturbed habitats embedded in dispersal networks (Pearson, Ortega, Eren, & Hierro, 2018; Pyšek et al, 2015). As such, and although this may be counter‐intuitive on a first sight (Price & Pärtel, 2013), our findings are not in contradiction with the limiting similarity concept (MacArthur & Levins, 1967): the mechanisms of biotic resistance involving functional similarity (notably through competition) are indeed undermined by disturbance (Elton, 1958) as demonstrated with our model community (Leclerc et al, 2021). Importantly, our model community is also composed of multiple foundation species and prone to complex epibioses involving neutral to positive interactions, which also affect its invasibility (Bulleri et al, 2008; Leclerc & Viard, 2018).…”
Section: Discussionsupporting
confidence: 55%
“…Multiple succession trials and disturbance experiments of fouling communities in the study region suggested that most of the neocosmopolitans are opportunistic, stress‐tolerant or both (Leclerc et al, 2021; Leclerc, Viard, González‐Sepúlveda, et al, 2020). By analysing their traits, the present study confirms this hypothesis and provides further elements to disentangle associated mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…These ecological drivers include topography and micro-climate (elevation, slope, aspect, and water distance) and anthropogenic-related factors (distance to human paths, roads, settlements, land use, and population density). These factors could potentially influence the long-term habitat composition, structure, or function, that can be identified with the help of species distribution modeling [ 52 , [57] , [58] , [59] , [60] ], as well as potentially weaken species resilience to future disturbances [ [61] , [62] , [63] ].…”
Section: Introductionmentioning
confidence: 99%
“…The important ecological factors include altitude, slope, aspect, leaf litter, disturbances (e.g., proximity to settlements and frequency of fire) and vegetation or food resources (e.g., trees and grass). These factors may affect long-term forest composition, structure, or function (Franklin et al, 2002;Palik et al, 2002;Hessburg et al, 2016) and compromise resilience to subsequent disturbance (Radeloff et al, 2000;Hessburg et al, 2019;Leclerc et al, 2021).…”
Section: Introductionmentioning
confidence: 99%